Factors influencing prescribing by critical care physicians to heart failure patients in Egypt: a cross-sectional survey - Seif El Hadidi; Naglaa Samir Bazan; Stephen Byrne; Ebtissam Darweesh; Margaret Bermingham (SpringerOpen, 2022)
Abstract Background Heart failure (HF) guideline-led prescribing improves patient outcomes; however, little is known about the factors influencing guideline-led prescribing in critical care settings. This study used a cross-sectional survey to assess the factors that influence physicians when prescribing to heart failure patients in a critical care setting in Egypt. Results The response rate was 54.8%. The international HF guidelines were the primary source of prescribing information for 84.2% of respondents. Staff were more familiar with the latest guideline recommendations than associate staff (86.7% vs 36.8%, p = 0.012) and considered patient's perspectives more often (86.7% vs 26.3%, p = 0.036). Renal function was the clinical factor that most frequently influenced the prescribing of loop diuretics or renin-angiotensin-aldosterone system inhibitors. Pulmonary function influenced beta-blockers prescription. The most frequently cited barrier to guideline-led prescribing was the absence of locally drafted guidelines. A majority of prescribers agreed that implementation of clinical pharmacy services, physician education and electronic reminders may improve the implementation of guideline-led prescribing. Conclusions Although experienced physicians are familiar with and use international guidelines, physicians would welcome local guidance on HF prescribing and greater clinical pharmacist input.